IGF2BP2 gene polymorphism in patients with morbid obesity - Kargun, Kursat; Senol, Sefa; Kirkil, Cuneyt; Cambay, Zafer; Kara, Murat; Aygen, Erhan; Yilmaz, Mustafa (Allied Acad, 2017)
Background/Aim: In this study, it was aimed to determine the relationship between morbid obesity and insulin-like growth factor 2 mRNA-binding protein 2 (IGF2BP2) rs1470579 and rs4402960 gene polymorphisms. Materials and methods: Data from 100 consecutive patients who underwent surgery due to morbid obesity (MO) and 100 healthy volunteers with normal body mass index (BMI) were compared. DNAs obtained from blood samples were analysed by real-time polymerase chain reaction (PCR) for rs1470579 and rs4402960 gene polymorphisms. Results: While there were 62 (62%) female and 38 (38%) male patients, the healthy control group consisted of 57 (57%) women and 43 (43%) men. The mean ages of morbidly obese patients and healthy individuals were 41.2 +/- 7.8 (median=39, min=17, max=58) and 36.9 +/- 6.5 (median=37, min=20, max=51), respectively (p>0.05). The mean BMI of obesity and control groups were 44.9 +/- 11.2 and 23.2 +/- 2.7, respectively (p<0.05). No significant differences were found between morbidly obese patients and healthy individuals regarding IGF2BP2 rs1470579 and rs4402960 gene polymorphisms and allele frequencies (p>0.05). Conclusion: No significant differences were found between morbidly obese patients and healthy individuals regarding IGF2BP2 rs1470579 and rs4402960 gene polymorphisms and allele frequencies.
Keywords: IGF2BP2; Morbidly obese; rs1470579; rs4402960